Behavioral Management of Parents and Teachers and the Student’s Performance under the New Normal Education - Evangeline C. Sentillas; Rhyna M. Limpangog; Madeline V. Elorde; Vicenta C. Estapia; Delia A. Jariolne; Hazel M. Acuna; Jayson L. Jao; Cherrylyn Capampangan; Roberto Suson (International Journal on Integrated Education, 2022)
This research assessed the behavior management practices and learners’ behavior at home in relation to learners’ academic performance in identified schools in the Municipality of Trinidad, Bohol Division during School Year 2020-2021. The data revealed that although there is no significant relationship between behavior management practices of the parents and academic performance findings shows that the academic performance of the learners was above average. However, it can be noted that there is a significant relationship between learners’ behavior and students’ academic performance. Moreover, time-out was the topmost utilize behavior management of the parents and modeling was the least used. Followed by consequences, reinforcement and modeling. It can also be noted that the most common perceived behavioral problem of the learners argues with their parents. This implies, that there is a need to strengthen the behavior management practices of the parents to promote responsible and respectful learners. The researchers highly recommend that a constant communication with the teacher and parents will be necessary to address learners’ behavior. Further, training and workshops must also be employed in the school with parents to be familiar with the new behavior management strategies.